2021
DOI: 10.3390/ma14174978
|View full text |Cite
|
Sign up to set email alerts
|

Foamed Geopolymer Composites with the Addition of Glass Wool Waste

Abstract: This study examines foamed geopolymer composites based on fly ash from the Skawina coal-fired power plant in Poland. The paper presents the effect of adding 3% and 5% by weight of glass wool waste on selected properties of foamed geopolymers. The scope of the tests carried out included density measurements, compressive and bending strength tests, measurements of the heat conduction coefficient, and the results of measurements of changes in thermal radiation in samples subjected to a temperature of 800 °C. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 38 publications
3
9
0
Order By: Relevance
“…The pace of climate change that Earth’s inhabitants are struggling with is accelerating more and more, and the effects of these changes are noticeable to everyone. An important direction of development is therefore looking for new, more ecological materials, in particular those based on renewable raw materials [ 4 , 5 , 6 , 7 ]. One of the promising alternatives may be geopolymerization technologies with a much lower carbon footprint compared to traditional building materials [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pace of climate change that Earth’s inhabitants are struggling with is accelerating more and more, and the effects of these changes are noticeable to everyone. An important direction of development is therefore looking for new, more ecological materials, in particular those based on renewable raw materials [ 4 , 5 , 6 , 7 ]. One of the promising alternatives may be geopolymerization technologies with a much lower carbon footprint compared to traditional building materials [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of them may be geopolymers. The production of geopolymers releases much smaller amounts of CO 2 into the atmosphere, and it can be a real alternative to waste management from the energy or metallurgical sector (for example, fly ash, slag) or also other sectors such as the construction industry (for example, construction and demolition waste) or mining (for example, different mine tailings) [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, geopolymer materials have aroused more and more interest both in the scientific community and in various areas of industry, where they can be used [ 1 , 2 , 3 ]. Geopolymers belong to the group of synthetic inorganic polymers, which are obtained in the process of alkaline activation of aluminosilicates, e.g., fly ash, metakaolin, red mud, and others [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The geopolymer precursor material may be an appropriate replacement to the traditional Portland cement [ 80 , 81 ]. It contains geological source material with silicon and aluminum content and a caustic activator to form a binder [ 82 , 83 ]. In 2017, a study revealed that waste rock wool is an ideal replacement for slag and fly ash from iron and metal to produce geopolymer concrete due to its high silicon and aluminum content [ 34 ].…”
Section: Repurposing As Fillers In Compositesmentioning
confidence: 99%